A Novel Technique for Improving Bodily Experience in a Non-operable Super–Super Obesity Case - Serino, Silvia; Scarpina, Federica; Keizer, Anouk; Pedroli, Elisa; Dakanalis, Antonios; Castelnuovo, Gianluca; Chirico, Alice; Novelli, Margherita; Gaudio, Santino; Riva, Giuseppe (Frontiers in Psychology, 2016)
Introduction: The available clinical guidelines for super-super obese patients (i.e., with body mass index (BMI) > 60 kg/m2) that are not suitable for bariatric surgery mandate a palliative multidisciplinary treatment (i.e., production and maintenance of weight loss) provided in a center of excellence. However, the modality and the impact of this approach are still controversial. Moreover, it is not able to address the high level of body dissatisfaction and body distortions that are common among these patients. Clinical Presentation: We report the case of a non-operable super-super obesity - a 37 year old woman with a BMI of 62 kg/m2 - receiving a specialized treatment for her obstructive sleep apnea. She entered a multidisciplinary program that promoted healthy behaviors, including physical activities and psychological intervention. To improve body dissatisfaction, which was linked to a significant multisensory impairment of body perception, she also entered a virtual reality (VR) body-swapping illusion protocol. At the end of the current investigation, the patient continued her multidisciplinary program, reporting an increase in the motivation for undertaking healthy behavior and a decrease in the anxiety feelings associated with her clinical condition. Conclusions: This case provides preliminary evidence that both body dissatisfaction and body-size distortions of non-operable super-super obesity patients could be addressed by a VR body-swapping protocol, which is important because the palliative multidisciplinary treatment recommended for these patients is not able to address them. Interestingly, the use of a VR body-swapping illusion protocol seems to be able to improve not only the experience of the body in these patients but their motivation for change.